The Use of Quizizz Applications and Its Impact on Higher Order Thinking Skills of Elementary School Teacher Education Students in Elementary Science Learning - Rizki, Etie Novia; Haryanto, Haryanto; Kurniawati, Wahyu (Universitas Pendidikan Ganesha, 2022)
Higher-order thinking skills (HOTS), which should develop in even semester students of PGSD in science learning, have experienced problems due to distance learning during the Covid-19 pandemic. This study aims to analyze the effect of using the Quizizz media application on Higher order thinking skills (HOTS) of PGSD students in science learning. This type of research is a quasi-experimental (quasi-experimental) design with Pretest-Posttest Control Group Design. The population used is the even semester students of the experimental class A2 and the control class A1 totaling 68 students. Sampling using a purposive sampling technique and collecting data using tests and observations. The instrument used in the study was an objective test question: the data analysis technique used descriptive, normality, homogeneity, hypothesis, and ANOVA tests. The results showed that the average score of the post-test results using Quizizz was higher than the post-test scores using Kahoot. Thus, it can be concluded that the Quizizz media application affects students' Higher order thinking skill (HOTS) ability in science learning.